Differential Effects of Electroconvulsive Therapy on Patients with Schizophrenia Versus Depressive Disorder: Clinical Distinction Between Antipsychotic and Antidepressant Effects of Electroconvulsive Therapy - Naho Nakayama; Tatsuo Nakahara; Hideyuki Iwanaga; Manabu Hashimoto; Takako Mitsudo; Yoshiomi Imamura; Hiroko Kunitake; Yoshito Mizoguchi; Takefumi Ueno (Brain Sciences)
Objective: Electroconvulsive therapy (ECT) is utilized for treating psychiatric disorders, such as schizophrenia (SCZ), major depressive disorder (MDD), and bipolar disorder (BD). We aimed to compare pre- and post-ECT treatment outcomes between patients with SCZ and a combined group of patients with MDD and BD (MDD+BD) to assess the distinction between the antipsychotic and antidepressant effects of ECT. Methods: ECT was administered to patients with SCZ (n = 17) and those with MDD+BD (n = 7). Symptoms were evaluated using the brief psychiatric rating scale (BPRS), clinical global impression scale (CGI), and global assessment of functioning (GAF). Plasma brain-derived neurotrophic factor (BDNF) levels were also measured. Results: The BPRS, CGI, and GAF scores significantly differed after ECT compared with those before ECT in each patient group. However, no significant differences were observed between the groups for each disorder. No significant differences were observed in plasma BDNF levels between the groups at baseline and during ECT. At baseline, only depression scores were more favorable in the SCZ group, whereas positive symptoms and disorganization scores were higher in the MDD+BD group. During treatment, positive symptoms, activation, and disorganization items were significantly more favorable in the MDD+BD group compared with the SCZ group. Total BPRS scores were not associated with plasma BDNF levels; however, rating scores of the several items related to activation, resistance, and disorganization were positively correlated with BDNF levels. Conclusion: ECT effects on several clinical outcomes in the MDD+BD group were associated with plasma BDNF levels. These findings suggest that ECT may be more effective for treating MDD than SCZ.